Diversification of rice-based cropping system with high-value crops for increased productivity and profitability - Saha, Priyanka; Bohra, Jitendra Singh; Banjara, Tejram (Indian Farming, 2023)
As the world’s population grows, so does the demand for food, putting pressure on the existing farming system to produce more. Crop diversification is an approach of fulfilling rising food demand by increasing the number of crops or substituting one or more crop with other in a cropping system. Crop diversification is intended to provide a wider choice in the crop production in a given area so as to expand production related activities on various crops while also minimizing risk. Due to prolonged adoption of existing rice-wheat cropping system, soil fertility and soil health is deteriorating which ultimately is affecting the sustainable food grain production. To meet the ever-increasing population’s demand for cereal, pulses, and oilseeds, it was found that including oilseeds and pulses in a rice-based cropping sequence was more beneficial than cereal alone. Crop diversification can thus help to improve livelihoods, environmental stability, and financial prosperity.